2020
DOI: 10.14719/pst.2020.7.4.798
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenic complexity of septoria spot disease of wheat in northern Kazakhstan

Abstract: Northern Kazakhstan is the main zone of spring wheat cultivation where, 85 % of the cultivated area is located. There is not a single variety resistant to Septoria spot among the varieties approved for use. The frequency of epiphytoties of wheat diseases in the northern part of Kazakhstan is four cases every ten years. During the years of epiphytotic development of brown rust and Septoria spot with the dominance of a particular disease, the yield of spring wheat is reduced by 25 % or more. Knowledge of the spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 4 publications
1
11
0
Order By: Relevance
“…Judging by restoration of the resistance of some lines and reduction in the proportion of susceptible ones in 2018-2019, some pathogen strains were eliminated from the population. It had been previously shown that P. nodorum prevailed in Northern-eastern Kazakhstan in 1994-2011 [25], but in 2018-2019, it was Z. tritici that dominated in Northern Kazakhstan [52]. These confirms our conclusion that the increased harmfulness of Septoria leaf blotch in the Omsk region was caused by changes in Z. tritici population.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Judging by restoration of the resistance of some lines and reduction in the proportion of susceptible ones in 2018-2019, some pathogen strains were eliminated from the population. It had been previously shown that P. nodorum prevailed in Northern-eastern Kazakhstan in 1994-2011 [25], but in 2018-2019, it was Z. tritici that dominated in Northern Kazakhstan [52]. These confirms our conclusion that the increased harmfulness of Septoria leaf blotch in the Omsk region was caused by changes in Z. tritici population.…”
Section: Discussionsupporting
confidence: 89%
“…The studies of Septoria blotch development in Northern Kazakhstan showed that all commercial wheat cultivars were susceptible to the disease [52]. The accessions of Th.…”
Section: Discussionmentioning
confidence: 99%
“…During the two-year study of species diversity of Septoria spot pathogens, Z. tritici was predominant, followed by S. nodorum and S. avenae f. sp. triticea [ 5 ]. This study has significance for future wheat breeding in Kazakhstan.…”
Section: Discussionmentioning
confidence: 99%
“…Annually, on average, about 13.0 million tons of grain are produced in Kazakhstan. The average grain yield is 1.1 tons per hectare (Babkenova et al, 2020). Septoria leaf blotch is one of the most destructive fungal pathogen of wheat in all wheat-producing areas (Toropova et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The destruction of chloroplasts and the shrink of the assimilation area of the leaf lead to the reduction of photosynthesis activity and the diminution of respiratory activity (Melkumov, Brazhnikova, 2018). Yield losses occur mainly as a result of grain content decrease within the single ear and decrease of grain weight in general (Babkenova et al, 2020). Septoria tritici and Stagonospora (Septoria) nodorum cause significant crop loss and severely reduce grain quality.…”
Section: Introductionmentioning
confidence: 99%